Spontaneous Intraparenchymal Tension Pneumocephalus - Seo, Hyukjoon; Kim, Sang Hoon; Ryu, Jiwook; Lee, Sung Ho (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Tension pneumocephalus is a treatable emergency that is usually caused by trauma or surgery. We present a rare case of spontaneous tension pneumocephalus. A 64-year-old woman presented with a severe aggravating headache. Computed tomography revealed a large air collection in the brain parenchyma of the right frontal lobe, both lateral ventricles, and the subarachnoid space. Emergent craniotomy was performed because her headache got progressively worse. We found that an abnormal bony protrusion connected the frontal sinus mucosa and the intraparenchymal pneumocephalus. After removal of the bony mass and repair of the defect, the patient immediately recovered and there was no recurrence.
Keywords: brain; pneumocephalus; surgery